Effects of different fertilizer application regimes and nitrogen rates on weed composition, growth performance and yield of forage corn - Obaidurahman, Zahid (2021)
Fertilizer management is an important consideration in corn production system because it is essential for the crop's growth and development. Moreover, another key focus for improving fertilizer use efficiency and increasing corn productivity is timing of fertilizer application at suitable crop growth stage. Furthermore, optimum nitrogen rates and plant density ensures the plants to grow properly both in their aboveground and belowground parts through efficient utilization of solar radiation and nutrients. In addition, weeds are one of the most important limiting factors in corn production, causing significant yield losses worldwide. The need to increase the supply of corn to meet with the increasing demand has called for better crop management practices including fertilizer and weed management strategies to enhance crop productivity. Therefore, two experiments were conducted in Field 15, Faculty of Agriculture, Universiti Putra Malaysia in open field. The first experiment evaluated two hybrid forage corn varieties (GWG888, CP888) responded to four fertilizer application regimes, namely T1 (applied at 1, 3 and 4 weeks after sowing (WAS)), T2 (2, 4 and 6 WAS), T3 (2, 4, 6 and 8 WAS), and T4 (2, 4. 8 and 10 WAS), to determine the best fertilizer application regime for corn growth, yield and weed management. In experiment 2, two levels of planting density (66667 Plants/ha and 76923 Plants/ha) as main plot and four levels of nitrogen fertilizer (120 kg/ha, 140 kg/ha 160 kg/ha and 180 kg/ha) as subplot were used to quantify the selected variety of forage corn growth and yield, and its effect on weed composition. The soil was thoroughly ploughed and pre-germinated seeds was sown in the field. The experiments were carried out in a split plot randomized complete block design with three and four replications, respectively. Data was recorded for number of leaves per plant, leaf area, plant height, chlorophyll content, cob length, number of cobs per plant, leaf, stem, cob and total plant fresh and dry matter yield, NPK, CP, NDF, ADF and lignin analysis in plant samples, number of weed species, weed population, weed flora composition and weed diversity index. Collected data were analyzed using SAS 9.4 software. The data were analyzed with variance analysis (ANOVA). Tukey’s Honestly Significant Difference (HSD) was used to compare significant differences (P≤0.05) among treatments. Results of experiment 1 showed that both factors (fertilizer application regimes and variety) were significantly influenced corn growth, yield and weed composition. Results indicated that T3 for GWG corn variety produced the highest values of plant height, leaf area, total DM yield, and % of crude protein % as compared to other treatments. Meanwhile, T1 showed the lowest plant height, leaf area, DM yield and % of crude protein. The highest weeds density obtained from late application of fertilizers T4. Results from second experiment indicated that application of 160 kg N/ha in lower plant density (66667 Plants/ha) produced the highest leaves number, plant height, cob length, and N, P and K content, followed 180 kg N/ha and 140 kg N/ha and the lowest obtained from 120 kg N/ha. Although, fresh and dry yield was greater in higher plant density (76923 Plants/ha). In addition, the ADF, NDF, and lignin content were significantly decreased with the highest application of N (180 kg N/ha). As N rates increased, the species, population and diversity of weed enhanced. The highest weeds population was obtained when 180 kg N/ha was applied. In conclusion, based on results obtained, suitable fertilizer application regime of 160 kg N/ha (T3) improved corn growth and yield. Besides, optimum nitrogen rate (160 kg N/ ha) in higher density (76923 Plants/ha) enhanced corn production.